2021
DOI: 10.1097/jxx.0000000000000657
|View full text |Cite
|
Sign up to set email alerts
|

A policy analysis of nurse practitioner scope of practice in Massachusetts

Abstract: Nurse practitioner (NP) practice has evolved since inception of the role in 1965. Educational requirements have been standardized requiring a master's degree, yet variation in NPs scope of practice exists across the United States. As the population ages and more Americans have health insurance coverage, the demand for health care continues to increase. Shortages of clinical providers and changes in hospital models of care continue to burden the health care system. Nurse practitioners have been found to provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In the US, the scope of NPs practice reflects state regulations, which have either full, reduced or restricted practice authority, determining how independently an NP can practice [ 32 ]. Much of the literature suggests that full-practice authority is required for primary care NPs if they are to: improve patient access to primary care [ 28 , 30 , 33 , 46 ], particularly in low socioeconomic and rural areas [ 10 , 41 , 42 ], reduce hospitalisations [ 27 , 44 ], and reduce healthcare and training costs [ 1 , 11 , 33 , 44 , 88 ]. Strong organisational support for independent practice increases NP’s capacity to provide effective primary care, and improves teamwork among NPs and physicians [ 89 91 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the US, the scope of NPs practice reflects state regulations, which have either full, reduced or restricted practice authority, determining how independently an NP can practice [ 32 ]. Much of the literature suggests that full-practice authority is required for primary care NPs if they are to: improve patient access to primary care [ 28 , 30 , 33 , 46 ], particularly in low socioeconomic and rural areas [ 10 , 41 , 42 ], reduce hospitalisations [ 27 , 44 ], and reduce healthcare and training costs [ 1 , 11 , 33 , 44 , 88 ]. Strong organisational support for independent practice increases NP’s capacity to provide effective primary care, and improves teamwork among NPs and physicians [ 89 91 ].…”
Section: Resultsmentioning
confidence: 99%
“…This exploratory analysis supports that an NP/PharmD HTN clinic is feasible and provides care that is equitable to physician-led care. The role of the advanced practice nurse is ever-evolving (Coote et al, 2022; Cuccovia et al, 2021). Previous studies have also shown that NPs, PharmD, and interdisciplinary teams provide care for HTN and other chronic diseases that is equitable to that of physicians (Brown, 2017; Himmelfarb et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding these strides, FPA barriers continue, which include administrative issues, therapy restrictions, physician signature requirements and ongoing opposition (including lack of collegiality), prescribing concerns, uneven reimbursement, physician-only procedures, telehealth problems, and the end of emergency waivers 9,10. Some states are lagging in FPA advancement due to lack of cooperation between nursing, medicine, and policy makers or a dearth of regulatory self-advocacy and engagement on the part of APRNs 11-13.…”
Section: Barriers To Fpamentioning
confidence: 99%